Impact of gender on trait prioritization and food product profile (fufu) development in Nigeria: Guide to breeders - Madu, Tessy; Nwafor, Solomon; Onyemauwa, Nnaemeka; Ukeje, Blesing; Ejechi, Mercy; Okoye, Benjamin (National Root Crops Research Institute, Nigeria, 2023)
Cassava is a good source of dietary fiber and essential source of energy, and it is a food-security crop which fits well into the farming systems of the smallholder farmers in Nigeria; especially for women providing sustained means of livelihood. Fufu a staple food in the South East and North Central regions of Nigeria, usually described as a “wet paste” food product that can be sold in wet form as an intermediate product or fufu dough ready to eat. Demand-driven breeding strategies are fast gaining prominence in the agricultural research centers globally. It has become important to consider specific user groups and their desired trait preferences in order to develop product profiles to inform breeding decisions. This study integrates RTBfoods project outcomes on fufu to identify gendered trait preferences among consumers in Nigeria. Consumer testing of fufu was carried out among 300 consumers (65.66% and 34.33% women and men, respectively, with 150 from each region) who were invited to test five fufu products made from cassava varieties with different quality characteristics. Results show that the improved clones compared favorably, or were better, than the local results for roots and fufu mash assessment. Smoothness and mouldability ranked high in terms of importance, followed by stickiness, stretchability and color, while hardness/softness and aroma were ranked the lowest. These are expected to guide breeders in trait prioritization and enhance the adoption of improved varieties.